A Split-Lung Ex Vivo Perfusion Model for Time- and Cost-Effective Evaluation of Therapeutic Interventions to the Human Donor Lung - Nicholas J. S. Chilvers; Nicholas J. S. Chilvers; Jenny Gilmour; Marnie L. Brown; Lucy Bates; Chong Yun Pang; Henning Pauli; John Dark; Andrew J. Fisher; Andrew J. Fisher (Transplant International, 2024)
With the ongoing shortage of donor lungs, ex vivo lung perfusion (EVLP) offers the opportunity for objective assessment and potential therapeutic repair of marginal organs. There is a need for robust research on EVLP interventions to increase the number of transplantable organs. The use of human lungs, which have been declined for transplant, for these studies is preferable to animal organs and is indeed essential if clinical translation is to be achieved. However, experimental human EVLP is time-consuming and expensive, limiting the rate at which promising interventions can be assessed. A split-lung EVLP model, which allows stable perfusion and ventilation of two single lungs from the same donor, offers advantages scientifically, financially and in time to yield results. Identical parallel circuits allow one to receive an intervention and the other to act as a control, removing inter-donor variation between study groups. Continuous hemodynamic and airway parameters are recorded and blood gas, perfusate, and tissue sampling are facilitated. Pulmonary edema is assessed directly using ultrasound, and indirectly using the lung tissue wet:dry ratio. Evans blue dye leaks into the tissue and can quantify vascular endothelial permeability. The split-lung ex vivo perfusion model offers a cost-effective, reliable platform for testing therapeutic interventions with relatively small sample sizes.